‘Optimal’ cutoff selection in studies of depression screening tool accuracy using the PHQ‐9, EPDS, or HADS‐D: A meta‐research study - Brehaut, Eliana; Neupane, Dipika; Levis, Brooke; Wu, Yin; Sun, Ying; Ioannidis, John P. A.; Markham, Sarah; Cuijpers, Pim; Patten, Scott B.; Benedetti, Andrea; Thombs, Brett D. (International journal of methods in psychiatric research, 2023)
ObjectivesOptimal cutoff thresholds are selected to separate ‘positive’ from ‘negative’ screening results. We evaluated how depression screening tool studies select optimal cutoffs.MethodsWe included studies from previously conducted meta‐analyses of Patient Health Questionnaire‐9, Edinburgh Postnatal Depression Scale, or Hospital Anxiety and Depression Scale—Depression accuracy. Outcomes included whether an optimal cutoff was selected, method used, recommendations made, and reporting guideline and protocol citation.ResultsOf 212 included studies, 172 (81%) attempted to identify an optimal cutoff, and 147 of these 172 (85%) reported one or more methods. Methods were heterogeneous with Youden's J (N = 35, 23%) most common. Only 23 of 147 (16%) studies described a rationale for their method. Rationales focused on balancing sensitivity and specificity without describing why desirable. 131 of 172 studies (76%) identified an optimal cutoff other than the standard; most did not make use recommendations (N = 56; 43%) or recommended using a non‐standard cutoff (N = 53; 40%). Only 4 studies cited a reporting guideline, and 4 described a protocol with optimal cutoff selection methods, but none used the protocol method in the published study.ConclusionsResearch is needed to guide how selection of cutoffs for depression screening tools can be standardized and reflect clinical considerations.